NERVOUS COMPONENT OF ARTERIAL HYPERTENSION. PROSPECTS FOR PREVENTION AND REHABILITATION - Cherkasov , A.; Petrova , E. (EurasianUnionScientists, 2020)
The article provides a theoretical analysis of the causes of arterial hypertension, describes a 3-month observation of the initial stage of the development of hypertension and experiments on non-drug normalization of blood pressure on a group of volunteers. It was shown that arterial hypertension is associated with spastic conditions of the intervertebral muscles in the lower thoracic spine, which lead to compression of sympathetic nerves that control the transport of water through the kidneys and disturb the balance of fluid circulation through the circulatory system.Theoretical analysis and experimental data made it possible to formulate a hypothesis about the dominant role of disorders in the activity of the sympathetic part of the nervous system in the development of primary and persistent arterial hypertension. The possibility of prevention of arterial hypertension and non-drug rehabilitation of patients with this disease has been shown